Cirebon Coastal Adolescents' Use of Taboo Language and Its Relation to Parental Education - Defina Defina; Risda Rizkilah; Dwi Hastuti (Universitas PGRI Sumatera Barat, 2024)
The prevalence of taboo language among adolescents, both at home and in school settings, is undeniable. Often, adolescents resort to using taboo words not only in moments of anger but also in non-angry contexts. This study endeavors to elucidate the patterns of taboo language usage among adolescents residing in the coastal area of Cirebon, taking into account the influence of parental education. Conducted at SMAN 1 Suranenggala and SMKN 1 Gunungjati, North Cirebon, the research involved a total sample of 195 respondents selected through cluster random sampling techniques. Findings indicate that a majority of adolescent boys and girls employ Javanese language at home, with taboo language predominantly falling within the low category of usage. Moreover, male adolescents exhibit a higher propensity for taboo language usage compared to their female counterparts, particularly in interactions with friends. Interestingly, the study discerns no significant correlation between the use of taboo language and parental education levels. Notably, taboo language predominantly revolves around animal-related terms, including dogs and their synonyms, pigs, and monkeys. Ultimately, the research underscores that the utilization of taboo language is contingent upon various factors such as situational contexts, environments, and conversational partners.